Photonic Microwave Generation Based on an OISL by Subharmonic Modulation From an OEO - Lin, Xiao-Dong; Xia, Guang-Qiong; Yang, Ti-Lian; Deng, Tao; Tang, Xi; Fan, Li; Gao, Zi-Ye; Wu, Zheng-Mao (IEEE photonics technology letters, 2019)
Photonic generation of a low-phase-noise microwave signal based on period-one (P1) dynamics of an optically injected semiconductor laser (OISL) subject to subharmonic modulation from an optoelectronic oscillator (OEO) is firstly proposed and experimentally demonstrated. Under suitable injection parameters, an OISL can be driven into period-one (P1) dynamics, which can be regarded as a photonic microwave with a relatively large linewidth. By further introducing an OEO with a frequency of 1/2 P1 frequency to directly modulate the OISL, a low-phase-noise photonic microwave with P1 frequency can be obtained. For an OISL operating at P1 oscillation with a frequency of 16.96 GHz, after imposing a 1/2 subharmonic modulation of 8.48 GHz on the OISL by an OEO, the photonic microwave linewidth is reduced from 5.23 MHz to less than 1 kHz, and the single sideband (SSB) phase noise of the final photonic microwave is -102.5 dBc/Hz@10 kHz, which is close to the SSB phase noise of the OEO signal (-104.3 dBc/Hz@10 kHz).